2014
DOI: 10.2308/ajpt-50698
|View full text |Cite
|
Sign up to set email alerts
|

On Being Professional in the 21st Century: An Empirically Informed Essay

Abstract: SUMMARY The purpose of this article is to reflect on the ongoing transformation of the Big 8/6/5/4 public accounting firms, with the intent of helping primarily doctoral students and junior faculty engaged in developing their own research programs. Drawing on a variety of theoretical research traditions that we have employed in our field research spanning over 30 years, we will briefly reconsider three “moments” through which the phenomenon of the multi-discipline (or, as termed in the sociology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 53 publications
0
32
1
Order By: Relevance
“…When this occurs, experts' opinions may be motivated by their self‐interest, which can lead to selection or focus of evidence that supports their opinions. Evidence of such behavior is prevalent in auditing as well as other disciplines (e.g., environmental, politics, policymaking, etc.,) (e.g., Lynn ; Malsch and Gendron ; Mumpower and Stewart ; Murphy ; Spence and Carter ; Dirsmith et al ) . Consequently, the expertise literature posits that differences in incentives, often influenced by an expert's institutional affiliation, whether it be the audit firm or the PCAOB, are another important factor likely to contribute to differences of opinion among experts (Hammond ; Murphy ; Mumpower and Stewart ).…”
Section: Background Theoretical Foundation and Research Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…When this occurs, experts' opinions may be motivated by their self‐interest, which can lead to selection or focus of evidence that supports their opinions. Evidence of such behavior is prevalent in auditing as well as other disciplines (e.g., environmental, politics, policymaking, etc.,) (e.g., Lynn ; Malsch and Gendron ; Mumpower and Stewart ; Murphy ; Spence and Carter ; Dirsmith et al ) . Consequently, the expertise literature posits that differences in incentives, often influenced by an expert's institutional affiliation, whether it be the audit firm or the PCAOB, are another important factor likely to contribute to differences of opinion among experts (Hammond ; Murphy ; Mumpower and Stewart ).…”
Section: Background Theoretical Foundation and Research Questionsmentioning
confidence: 99%
“…The existing audit literature also suggests that the different roles/affiliations between auditors and PCAOB inspectors can often lead to divergent views and opinions, even though many of the current inspectors were former auditors with similar training and experience who used to perform the work they are now inspecting (e.g., Glover et al ; Spence and Carter ; Dirsmith et al ; Malsch and Gendron ). We thank the editor for this insight.…”
mentioning
confidence: 99%
“…Similarly, auditors limit specialists' discretion over the audit procedures they perform. One auditor (M4) said, “I think it's a best practice to keep a pretty close rein on my specialists so that they focus on what's important and don't spend time in the weeds, per se.” Another auditor (P6) described keeping valuation specialists from “getting into the guts of the work.” Restricting specialists' access to information helps auditors control the abstract knowledge system, legitimizing auditors' claim to jurisdiction (Dirsmith et al ). Restriction also keeps specialists from accessing part of the knowledge system to build a competing claim (Abbott ).…”
Section: Auditors' Use Of Specialists In Audits Of Fair Valuesmentioning
confidence: 99%
“…Moreover, a much higher percentage of audit seniors reported that they would acquiesce to obedience pressure than predicted by the audit partners and managers who assisted us in developing the ethical scenarios. These partners and managers expressed a high level of confidence ex ante that audit seniors from their firm would generally not be susceptible to obedience pressure from a superior to perform or permit unethical acts, consistent with auditor ethical standards established by large audit firms’ centralized, bureaucratic controls (Gendron and Spira ; Dirsmith, Covaleski, and Samuel ). This prediction is clearly contradicted by our results, suggesting that the firms’ official “tone at the top” regarding ethical conduct is not uniformly reflected in subordinate auditors’ ethical choices at the local practice office level.…”
Section: Introductionmentioning
confidence: 82%
“…Organizational controls in public accounting are marked by tension between the more formal bureaucratic control imposed by administrative partners and the largely informal clan control applied by practice partners at the local office level (Gendron and Spira ; Dirsmith et al. ).…”
Section: Theory and Hypotheses Developmentmentioning
confidence: 99%